2009
DOI: 10.1105/tpc.108.063164
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Salicylate Production and Jasmonate Signaling Are Not Essential for Systemic Acquired Resistance inArabidopsis 

Abstract: Systemic acquired resistance (SAR) develops in response to local microbial leaf inoculation and renders the whole plant more resistant to subsequent pathogen infection. Accumulation of salicylic acid (SA) in noninfected plant parts is required for SAR, and methyl salicylate (MeSA) and jasmonate (JA) are proposed to have critical roles during SAR long-distance signaling from inoculated to distant leaves. Here, we address the significance of MeSA and JA during SAR development in Arabidopsis thaliana. MeSA produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
197
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(208 citation statements)
references
References 82 publications
6
197
3
2
Order By: Relevance
“…In a search for this mobile signal, it was proposed that locally produced SA is esterified to methyl salicylate (MeSA), which is transported to systemic tissues and there converted back to SA (Seskar et al 1998;Park et al 2007). However, Attaran et al (2009) demonstrated that in Arabidopsis the synthesis of MeSA does not coincide with the expression of SAR. Earlier, Maldonado et al (2002) suggested that a lipidbased molecule could function as the long-distance regulator of SAR in Arabidopsis.…”
Section: Systemic Acquired Resistance Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a search for this mobile signal, it was proposed that locally produced SA is esterified to methyl salicylate (MeSA), which is transported to systemic tissues and there converted back to SA (Seskar et al 1998;Park et al 2007). However, Attaran et al (2009) demonstrated that in Arabidopsis the synthesis of MeSA does not coincide with the expression of SAR. Earlier, Maldonado et al (2002) suggested that a lipidbased molecule could function as the long-distance regulator of SAR in Arabidopsis.…”
Section: Systemic Acquired Resistance Signalingmentioning
confidence: 99%
“…Moreover, a recent study by Jung et al (2009) suggests azelaic acid to be the transported mobile signal required for the systemic activation of SAR in Arabidopsis. Although also JA signaling occurs in the early response of SAR, JA biosynthesis, or downstream signaling are not required for the systemic expression of SAR (Truman et al 2007;Vlot et al 2008;Attaran et al 2009). …”
Section: Systemic Acquired Resistance Signalingmentioning
confidence: 99%
“…The existence of more than one signal capable of establishing a primed state suggests that plants may use a consortium of molecules to reach a certain 'priming threshold'. Responses to specific signals can depend on plant growth/infection conditions, which highlights the plasticity of plant responses 10,14,16,[20][21][22] .…”
mentioning
confidence: 99%
“…Accumulation of SA is often correlated with an increase in ROS production during plant stress response (for review, see Herrera-Vásquez et al, 2015). A series of SA binding proteins has been identified, notably catalase (Chen et al, 1993a), peroxidase (Durner and Klessig, 1995), and methyl-salicylate esterase (Forouhar et al, 2005) that appear to explain this correlation, but their roles as general SA receptors have been controversial (Attaran et al, 2009;Bi et al, 1995). Further sets of SA binding proteins in Arabidopsis have been identified by affinity screens and include several mitochondrial enzymes and also GSTs including GSTF8, which showed enzymatic inhibition by SA (Manohar et al, 2015;Tian et al, 2012).…”
mentioning
confidence: 99%